Blocking viral entry with bulevirtide reduces the number of HDV-infected hepatocytes in human liver biopsies - Allweiss, Lena; Volmari, Annika; Suri, Vithika; Wallin, Jeffrey J.; Flaherty, John F.; Manuilov, Dmitry; Downie, Bryan; Lütgehetmann, Marc; Bockmann, Jan-Hendrick; Urban, Stephan; Wedemeyer, Heiner; Dandri-Petersen, Maura (Journal of hepatology, 2024)
Background & Aims - Bulevirtide (BLV) is a first-in-class entry inhibitor and the only approved treatment for patients chronically infected with HDV in Europe. We aimed to investigate the efficacy of BLV treatment in paired liver biopsies obtained at baseline and after 24 or 48 weeks of treatment. - Methods - We performed a combined analysis of 126 paired liver biopsies derived from three clinical trials. In the phase II clinical trial MYR202, patients with chronic hepatitis D were randomised to receive 24 weeks of BLV at 2 mg, 5 mg or 10 mg/day. Patients in MYR203 (phase II) and MYR301 (phase III) received 48 weeks of BLV at 2 mg or 10 mg/day. Tenofovir disoproxil fumarate monotherapy or delayed treatment served as comparators. Virological parameters and infection-related host genes were assessed by qPCR and immunohistochemistry. - Results - At week 24, median intrahepatic HDV RNA decline from baseline was 0.9Log10 with 2 mg (n = 7), 1.1Log10 with 5 mg (n = 5) and 1.4 Log10 with 10 mg (n = 7) of BLV. At week 48, median reductions were 2.2Log10 with 2 mg (n = 27) and 2.7Log10 with 10 mg (n = 37) of BLV, while HDV RNA levels did not change in the comparator arms. Notably, a drastic decline in the number of hepatitis delta antigen-positive hepatocytes and a concomitant decrease in transcriptional levels of inflammatory chemokines and interferon-stimulated genes was determined in all BLV-treatment arms. Despite the abundance of HBsAg-positive hepatocytes, replication and covalently closed circular DNA levels of the helper virus HBV were low and remained unaffected by BLV treatment. - Conclusion - Blocking viral entry diminishes signs of liver inflammation and promotes a strong reduction of HDV infection within the liver, thus suggesting that some patients may achieve HDV cure with long-term treatment. - Impact and implications - Chronic infection with HDV causes the most severe form of viral hepatitis, affecting approximately 12 million people worldwide. The entry inhibitor bulevirtide (BLV) is the only recently approved anti-HDV drug, which has proven efficacious and safe in clinical trials and real-word data. Here, we investigated paired liver biopsies at baseline and after 24 or 48 weeks of treatment from three clinical trials to understand the effect of the drug on viral and host parameters in the liver, the site of viral replication. We found that BLV treatment strongly reduces the number of HDV-infected cells and signs of liver inflammation. This data implies that blocking viral entry ameliorates liver inflammation and that prolonged treatment regimens might lead to HDV cure in some patients. This concept will guide the further development of therapeutic strategies and combination treatments for patients with CHD. - Clinical trial numbers - NCT03546621, NCT02888106, NCT03852719
Online verfügbar: 8. Februar 2024, Artikelversion: 15. Mai 2024
Gesehen am 18.11.2024